Mucosal and systemic immunity to Campylobacter jejuni in rabbits after gastric inoculation. - Burr, D H (1988)
The mucosal and systemic immune responses to Campylobacter jejuni were studied in rabbits receiving gastric inoculation with live organisms. A lavage procedure was used to facilitate repeated monitoring of the intestinal immune response to C. jejuni. Immunity to C. jejuni was determined by secondary challenge by using the removable intestinal tie adult rabbit diarrhea (RITARD) model and monitoring for resistance to colonization and bacteremia. Oral-gastric inoculation of normal rabbits produced a transient intestinal colonization without diarrhea. C. jejuni serotypes differed in their ability to colonize the intestines of rabbits and to stimulate primary intestinal and serum antibody responses. Animals previously colonized were resistant to recolonization and the development of bacteremia after homologous challenge by the RITARD procedure but were not resistant to heterologous challenges. Anticampylobacter intestinal and serum IgA titers before this secondary infection were the most reliable predictors of resistance to colonization and bacteremia.